Docking studies of n-cycloalkyl-(cycloalkaryl)-2-[(3-R-2-OXO-2H- [1,2,4]triazino[2,3-c]quinazolin-6-YL)THIO]acetamides towards to COVID-19 - Antypenko, O. M.; Berest, G. G.; Kovalenko, S. I.; Антипенко, Олексій Миколайович; Берест, Галина Григорівна; Коваленко, Сергій Іванович (Тернопіль : ТНМУ, 2021)
There are seven coronaviruses known to infect people. Four of them are 229E, NL63, OC43, and HKU1 that typically cause a cold and only rarely result in death. The other three - MERS-CoV, SARSCoV, and the new SARS-CoV-2 - have varying degrees of lethality. In the 2003 SARS outbreak, 10 percent of infected people died. Between 2012 and 2019, MERS killed 23 percent of infected people. Although the case fatality rate of COVID-19 is lower, the virus has already killed more people than the other two outbreaks combined, which some have attributed to the pathogen’s fast transmission. That’s why search of new potential inhibitors of COVID-19 is up to date.